Answer:
Step-by-step explanation:
A quadratic equation in one variable given by the general expression:
Where:
The roots of this equation can be found using the quadratic formula, which is given by:
So:
As you can see, in this case:
Using the quadratic formula:
Therefore, the answer is:
Answer:
7 notepads
Step-by-step explanation:
5 + 3x = 26
Subtract constant (5)
3x = 21
Divide by coefficient (3)
x=7
Solving #19
<u>Take y-values from the graph</u>
- a) (g·f)(-1) = g(f(-1)) = g(1) = 4
- b) (g·f)(6) = g(f(6)) = g(2) = 2
- c) (f·g)(6) = f(g(6)) = f(5) = 1
- d) (f·g)(4) = f(g(4)) = f(2) = -2
Answer:
200 miles
Step-by-step explanation:
Answer:
x=4
Step-by-step explanation:
14=3x+2
Move all terms that don't contain x to the right side and solve.